Evaluation of the clinical performance of OncoPredict HPV® SCR assay within the VALGENT‐2 framework. Issue 1 (27th December 2022) - Dhillon, Sharonjit K.; Cocuzza, Clementina E.; Chung, Pui Yan Jenny; Martinelli, Marianna; Giubbi, Chiara; Njoku, Ruth C.; Bhatia, Ramya; Cuschieri, Kate; Arbyn, Marc
Abstract: Human papillomavirus (HPV) assays used in cervical cancer screening should be clinically validated according to international criteria. OncoPredict HPV® Screening (SCR) is a partial genotyping multiplex real‐time PCR assay targeting E6/E7 genes of 13 high‐risk (hr) HPVs. OncoPredict HPV® SCR (index assay) identifies HPV‐16 and HPV‐18 separately, 11 other hrHPV in aggregate and includes quality controls for sample adequacy, DNA extraction efficiency and PCR inhibition. 1300 VALGENT‐2 study samples (from women aged 20–60 attending the Scottish cervical cancer screening program) were tested with the index assay and the GP5+/6+ PCR enzyme immunoassay (standard comparator assay). Non‐inferior accuracy detecting cervical intraepithelial neoplasia of grade 2 or worse (CIN2+) of the index versus comparator was verified. Intra‐ and interlaboratory reproducibility of the index was evaluated by overall concordance and Cohen's kappa, using a sub‐population ( n  = 526). Relative sensitivity and specificity for CIN2+ of the index versus comparator were 1.01 (95% confidence interval [CI]: 0.99–1.03) and 1.02 (95% CI: 1.0–1.04), respectively. Noninferiority p  values were all ≤0.05, except for CIN3+ in patients ≥30 years. Excellent intra‐ and interlaboratory reproducibility was shown with concordance >98% and kappas >0.95. OncoPredict HPV® SCR fulfills the three international validation criteria for hrHPV DNA tests in cervical cancer screening.